2017
DOI: 10.26582/k.49.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a one-session-per-week physical education-based stretching program on hamstring extensibility in schoolchildren

Abstract: Abstract:The purpose of this study was to examine the effects of a one-session-per-week stretching program on hamstring extensibility among schoolchildren in the physical education (PE) setting. Thirty seven 9-year-old schoolchildren from two classes were clustered and randomly assigned to an experimental group (n=19) or a control group (n=18). During PE classes, the experimental students performed a 3-minute stretching program once a week throughout academic year (a total of 32 calendar weeks, but 28 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…Since static stretching technique has been mainly recommended for schoolchildren, up-to-date studies carried out with schoolchildren have used static stretching techniques to improve children's flexibility (e.g. Mayorga-Vega, et al, 2014b;Merino-Marban, et al, 2015;Sanchez Rivas, et al, 2014). The practice of dynamic stretching techniques has been avoided in work with young people because of a greater potential risk of muscle injury (Behm, et al, 2008;Faigenbaum, et al, 2009).…”
Section: Development Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Since static stretching technique has been mainly recommended for schoolchildren, up-to-date studies carried out with schoolchildren have used static stretching techniques to improve children's flexibility (e.g. Mayorga-Vega, et al, 2014b;Merino-Marban, et al, 2015;Sanchez Rivas, et al, 2014). The practice of dynamic stretching techniques has been avoided in work with young people because of a greater potential risk of muscle injury (Behm, et al, 2008;Faigenbaum, et al, 2009).…”
Section: Development Programmentioning
confidence: 99%
“…Regrettably, as far as we know research studies examining the effect of flexibility detraining are really scarce and contradictory (Cipriani, Terry, Haines, Tabibnia, & Lyssanova, 2012;Rancour, Holmes, & Cipriani, 2009;Willy, Kyle, Moore, & Chleboun, 2001), especially among school-age children Merino-Marban, et al, 2015). While several previous studies showed that, after a shortterm stretching program, individuals' flexibility levels reverted to their baseline after 4-5 weeks of detraining Willy, et al, 2001), other research studies found that individuals retained significant gains (Cipriani, et al, 2012;Mayorga-Vega, et al, 2014b;Rancour, et al, 2009). PE teachers must also face other planning-related problems when intending to develop students' flexibility levels .…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have gone further and have wondered how long they can retain these gains after a program of several weeks [26,35,36]. Current scientific information about the flexibility detraining is really scarce and contradictory [37,38,39], especially among school age children [35,36,26].…”
Section: Re-test Programsmentioning
confidence: 99%
“…Current scientific information about the flexibility detraining is really scarce and contradictory [37,38,39], especially among school age children [35,36,26]. Previous studies that carried out a PEbased stretching program observed statistically significant lost of hamstring extensibility after five weeks of detraining [35,36,26]. Although MayorgaVega et al [36] (2014d) observed that schoolchildren retained significant gains, most of previous studies also found that children' flexibility levels decreased to baseline [35,26].…”
Section: Re-test Programsmentioning
confidence: 99%
See 1 more Smart Citation